Taxing the residual profit of multinational enterprises: A critique of formulaic apportionment and a proposal - Wolfram F. Richter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
According to plans put forward by the OECD/G20 Inclusive Framework on BEPS, a share of residual profit earned by eligible MNEs is to be taxed by market jurisdictions. For this purpose, revenue-based formulaic apportionment of residual profit is proposed. This note argues against the use of a rule requiring the multilateral assessment of MNEs' worldwide profit and recommends an alternative method of sharing taxing rights with market jurisdictions. The proposed method relies on unilateral profit splitting and is suggested by the application of Shapley value theory to the fair and equitable division of taxing rights between cooperating jurisdictions.
Keywords: H25; M48; F23; 330; BEPS Project; Pillar One; formulaic apportionment; profit splitting; cooperative game theory